1983
DOI: 10.1161/01.res.53.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Vanadate effect on the Na,K-ATPase and the Na-K pump in in vitro-grown rat vascular smooth muscle cells.

Abstract: The impact of vanadate on the Na,K-ATPase system in the vascular smooth muscle cell is poorly understood. The present study describes the kinetics of the effect of vanadate on Na,K-ATPase and the Na-K pump in in vitro grown rat VSMC's. Vanadate interaction with the Na,K-ATPase system in vascular smooth muscle cells was examined by observing its influence on ouabain-sensitive adenosine triphosphate hydrolysis in disrupted cells rendered permeable by osmotic shock, and the uptake of rubidium by intact cells. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Sodium vanadate also caused tension development in the presence of high concentration of ouabain, as has been reported in vascular smooth muscles (Ozaki & Urakawa, 1979 ;Hudgins & Bond, 1981;Rapp, 1981). Moreover, it has been reported that even though vanadate is taken into vascular smooth muscle cells, there is no inhibition of Na, K-ATPase (Searle et al, 1983). This also supports the contractile action of vanadate without inhibition of N a, K-ATPase.…”
Section: Discussionsupporting
confidence: 81%
“…Sodium vanadate also caused tension development in the presence of high concentration of ouabain, as has been reported in vascular smooth muscles (Ozaki & Urakawa, 1979 ;Hudgins & Bond, 1981;Rapp, 1981). Moreover, it has been reported that even though vanadate is taken into vascular smooth muscle cells, there is no inhibition of Na, K-ATPase (Searle et al, 1983). This also supports the contractile action of vanadate without inhibition of N a, K-ATPase.…”
Section: Discussionsupporting
confidence: 81%
“…The IC 50 value observed in the present experiments with genistein on the ATP-sensitive K + channel corresponds well to those previously obtained. To judge from the present and other experiments on sodium orthovanadate, a tyrosine phosphatase inhibitor as well as a blocker of Na + -K + ATPase and Ca 2+ ATPase (Searle et al, 1983;Raeymaekers et al, 1983), current augmentation by vanadate is not speciĀ®c to the voltage-dependent Ca 2+ channel, but also a ects various K + currents, including the pinacidil-induced K + current in vascular smooth muscle cells (Wijetunge et al, 1992;Xiong & Cheung, 1995;Hatakeyama et al, 1996). Augmentation of such ionic currents by orthovanadate and their inhibition by genistein, but not by daidzein, is fully consistent with the e ects being produced via tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 91%
“…Vanadate can also inhibit SERCA and H Ļ© pumps; however, with our protocol, SERCA was already inhibited by CPA and no effect of vanadate on cell pH was observed over the experimental time course (data not shown). Another consideration in using vanadate is its ability to permeate the cell (25); however, treatment with vanadate clearly altered Ca 2Ļ© clearance, indicating at least partial effects on PMCA. Thus, with the caveat that no inhibitor is perfectly specific, our evidence suggests that the effects of vanadate reported here reflect the inhibition of PMCA.…”
Section: Discussionmentioning
confidence: 99%